Inhibition of Hypoxia Inducible Factor Alpha and Astrocyte-Elevated Gene-1 Mediates Cryptotanshinone Exerted Antitumor Activity in Hypoxic PC-3 Cells. (29th November 2012) - Lee, Hyo-Jeong; Jung, Deok-Beom; Sohn, Eun Jung; Kim, Hanna Hyun; Park, Moon Nyeo; Lew, Jae-Hwan; Lee, Seok Geun; Kim, Bonglee; Kim, Sung-Hoon
Abstract : Although cryptotanshinone (CT) was known to exert antitumor activity in several cancers, its molecular mechanism under hypoxia still remains unclear. Here, the roles of AEG-1 and HIF-1 α in CT-induced antitumor activity were investigated in hypoxic PC-3 cells. CT exerted cytotoxicity against prostate cancer cells and suppressed HIF-1 α accumulation and AEG-1 expression in hypoxic PC-3 cells. Also, AEG-1 was overexpressed in prostate cancer cells. Interestingly, HIF-1 α siRNA transfection enhanced the cleavages of caspase-9, 3, and PAPR and decreased expression of Bcl-2 and AEG1 induced by CT in hypoxic PC-3 cells. Of note, DMOG enhanced the stability of AEG-1 and HIF-1 α during hypoxia. Additionally, CT significantly reduced cellular level of VEGF in PC-3 cells and disturbed tube formation of HUVECs. Consistently, ChIP assay revealed that CT inhibited the binding of HIF-1 α to VEGF promoter. Furthermore, CT at 10 mg/kg suppressed the growth of PC-3 cells in BALB/c athymic nude mice by 46.4% compared to untreated control. Consistently, immunohistochemistry revealed decreased expression of Ki-67, CD34, VEGF, carbonic anhydrase IX, and AEG-1 indices in CT-treated group compared to untreated control. Overall, our findings suggest that CT exerts antitumor activity via inhibition of HIF-1 α, AEG1, and VEGF as a potent chemotherapeutic agent. Erratum to "Inhibition of Hypoxia Inducible Factor Alpha and Astrocyte-Elevated Gene-1 Mediates Cryptotanshinone Exerted Antitumor Activity in Hypoxic PC-3 Cells" dx.doi.org/10.1155/2013/267352